Blockchain-Based Digital Transaction Security System: Perspective of Imam al-Shāṭibi’s Maqāṣid al-Sharī’ah Concept - Yasin, Achmad; Billah, Arifah (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
Blockchain is a technological advancement that does not yet have regulatory certainty, especially regarding taxation and its use in certain domains does not fulfill shari'ah provisions. This research is a literature study that explain the benefits of blockchain technology when applied in the Islamic economic sector and analyses it based on maqasid al-shari'ah according to Imam al-Shatibi. The method implemented: normative law with a statutory and conceptual approach. Data collection is done through literature research and documentation. This research analyses that the benefits of using blockchain technology in Islamic economics provides various significant advantages for human welfare, so it is considered maṣlahah. Applying this technology to economic activities is a form of jalbu al-masalih. Blockchain technology increases the operational ease of digital transactions and provides vigorous wealth protection through tokens generated from digitizing tangible assets. The blockchain application in digital transactions isa form of dar'u al-mafasid. Analysed from the perspective of Imam al-Shatibi's maqasid al-shari'ah, the blockchain technology efficiency and security for data and information in the digital transaction ledge rare included as hajiyyah needs. Its use that facilitates cryptocurrency transactions is highlighted as haram because of its destruction of religion due to its prohibition. The protection afforded to real-world asset tokens and their overall usefulness elevates this technology's status as a daruriyyah min janibi al-adam (protection of primary needs from absence).